2002
DOI: 10.1038/sj/cdd/4400945
|View full text |Cite
|
Sign up to set email alerts
|

Induction of apoptosis by chemotherapeutic drugs: the role of FADD in activation of caspase-8 and synergy with death receptor ligands in ovarian carcinoma cells

Abstract: Although ovarian tumours initially respond to chemotherapy, they gradually acquire drug resistance. The aims of this study were to identify how chemotherapeutic drugs with diverse cellular targets activate apoptotic pathways and to investigate the mechanism by which exposure to a combination of drugs plus death receptor ligands can increase tumour cell kill. The results show that drugs with distinct cellular targets differentially up-regulate TRAIL and TNF as well CD95L, but do not require interaction of these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
33
0
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 18 publications
2
33
0
1
Order By: Relevance
“…After 48 h, FACS analysis was performed to determine the degree of cell death induced and the relative amounts of apoptosis and necrosis. Figure 2B demonstrates that the mode of cell death induced by activated CB1954 in this setting was predominantly apoptosis, in common with a range of other chemotherapeutic agents (data not shown and Milner et al, 2002). In addition, RAd-NR infected SKOV3 cells were treated with CB1954 and similar analysis was performed.…”
Section: Resultsmentioning
confidence: 67%
See 3 more Smart Citations
“…After 48 h, FACS analysis was performed to determine the degree of cell death induced and the relative amounts of apoptosis and necrosis. Figure 2B demonstrates that the mode of cell death induced by activated CB1954 in this setting was predominantly apoptosis, in common with a range of other chemotherapeutic agents (data not shown and Milner et al, 2002). In addition, RAd-NR infected SKOV3 cells were treated with CB1954 and similar analysis was performed.…”
Section: Resultsmentioning
confidence: 67%
“…We have previously shown that at a concentration of 50 mM, DEVD-FMK (caspase-3 inhibitor), IETD-FMK (caspase-8 inhibitor) and LEHD-FMK (caspase-9 inhibitor) work in a specific manner (Milner et al, 2002). Therefore, this concentration was used for all the inhibitors in these experiments.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, administration of proteasome inhibitors results in the stimulation of a proapoptotic autocrine loop by signaling via death receptor family members. However, as Milner et al had shown previously [53], genotoxic stress induced by chemotherapeutic drugs can differentially upregulate TRAIL, TNF and CD95L and activate caspase-8 in a FADDindependent manner without engagement of their receptor partners.…”
Section: Discussionmentioning
confidence: 86%